PENCAPAIAN DAN SUMBANGAN ALUMNI AKADEMI PENGAJIAN ISLAM UNIVERSITI MALAYA (APIUM) DALAM PENGAJIAN SYARIAH DI MALAYSIA: Achievements and Contributions of APIUM Alumni to Shariah Studies in Malaysia - Mohamed Adil, Mohamed Azam; Mansor, Muhamad Sayuti (Jurnal Syariah, 2022)
The Academy of Islamic Studies (APIUM), University of Malaya, is one of the most prominent shariah institutions in this country. Since its inception, APIUM has produced thousands of alumni in the field of Islamic studies, particularly shariah. This article, thus, seeks to explore the achievements and contributions made by these alumni in developing and reviving the study of shariah in Malaysia. For this aim, this study will first examine the long history of APIUM followed by its methodological approach in studying shariah. Next, it will closely identify individual contributions and achievements of its alumni in various sectors related to shariah. Overall, this study finds that alumni from APIUM have contributed immensely to the development of shariah studies in this country. This is done through APIUM’s unique approach towards Shariah studies, and the important roles played by its alumni in key areas such as fatwa institutions, Islamic judiciary, shariah scholarship, Islamic administration, and Islamic finance.